2023
DOI: 10.1039/d3sc00734k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic generation of ortho-quinone dimethides via donor/donor rhodium carbenes

Abstract: Substrates engineered to undergo a 1,4-C–H insertion to yield benzocyclobutenes resulted in a novel elimination reaction to yield ortho-quinone dimethide (o-QDM) products that undergo Diels-Alder or hetero-Diels-Alder cycloadditions. The analogous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a study with the Tambar group involving the oxonium ylide shown, we again predicted a preference for [Rh]-free rearrangement, and again no competing [Rh]-bound transition structure was found. Finally, in another study with the Shaw group, we predicted [Rh]-free [4 + 2] cycloaddition. Note that the ylide in this case can also be formulated as an ortho -quinodimethide.…”
Section: Should I Stay or Should I Go Now?mentioning
confidence: 97%
“…In a study with the Tambar group involving the oxonium ylide shown, we again predicted a preference for [Rh]-free rearrangement, and again no competing [Rh]-bound transition structure was found. Finally, in another study with the Shaw group, we predicted [Rh]-free [4 + 2] cycloaddition. Note that the ylide in this case can also be formulated as an ortho -quinodimethide.…”
Section: Should I Stay or Should I Go Now?mentioning
confidence: 97%
“…16b More recently, the Shaw group reported the catalytic formation of o -QDMs from rhodium carbene intermediates, with subsequent interception of the o -QDMs by various dienophiles (Scheme 1c ). 16c In the context of sultines as o -QDM precursors, the reactivity of sultines with glyoxylates in an oxa-DA reaction has been reported only as part of a synthetic effort toward heteroanthracycline antitumor drugs. 17 An exceedingly high equivalence of oxa-dienophiles was required to obtain synthetically useful yields of isochromans.…”
Section: Table 1 Optimization Of the Reaction Parameter...mentioning
confidence: 99%